Identification and characterization of Enterocytozoon Bieneusi isolates from the proto—Malay and Senoi tribes in Sungai Lembing, Pahang - Azhari, Azah Ashikin (2016)
Enterocytozaon bieneusi is most common of microsporidian species that infects many types of cells including human and animals. These organisms are causing long lasting diarrhea primarily in immunocompromised patients but microsporidjosis is also higher in immunooompetent individuals. The previous study of microsporidial infection is mostly focused on immunodeficiency or immunosuppressive individuals. Information regarding microsporidial infections among immunocompetent individuals is lacking. Hence, this cross sectional study was carried out to determine prevalence of E‘ bieneusi infection and to find out the occurrence of E. bieneusi according to age group and gender among the Prom-Malay and Senoi tribes in Sungai Lembing, Pahang, Malaysia. Stool samples were collected fiom 209 voluntary participants; 96 males and 113 females that aged between one to 85 years old. Demographic data, socioeconomic, environmental, and behavioral infomation was collected by using pre-tested questionnaire. Overall prevalence of E‘ bieneusi infection was 3.83 % (8/209). From the observation, majority of individual infected with E. bieneusi was male (833 %) can be observed in those aged 215 years old‘ These samples were detected Small Subunit rDNA gene by using Polymerase chain reaction amplification with specific primer EBIEFl and EBIER], as demonstrated by an amplicon of 607-bp. This is the first report of E‘ bieneusi in Malaysia. It is hoped that these findings will allow greater emphasis from public health authrities through public education on personal hygiene and the consumption of boiled or filtered water in order to reduce the infection.